Mass transfer dynamics in soaking of chickpea. (June 2018) - Costa, Rui; Fusco, Francesca; Gândara, João F.M.
Abstract: Chickpea ( Cicer arietinum L.) is a widely-used pulse in industrial production of foods and home cooking with soaking being the most used operation in its processing. Insight into its mass transfer behavior enables the design of optimum processing conditions to achieve maximum quality and nutrient content. In this work, water gain and solids loss were modeled assuming ordinary diffusion. Water diffusivities vary between 1.12 × 10 −10  m 2 /s at 25 °C to 3.83 × 10 −10  m 2 /s at 100 °C. Solids diffusivities vary between 9.77 × 10 −11  m 2 /s and 4.07 × 10 −10  m 2 /s at 75 °C and 50 °C, respectively. Activation energies were calculated, assuming an Arrhenius model. Three periods of mass transfer have been identified, with the first characterized by a density increase and a solids loss until 5%. Hydrodynamic flow and diffusion occur simultaneously, both for water and solids transfer. The new insights gained with this work can support the development of more rigorous modeling of chickpea soaking, based on more accurate mass transfer mechanisms. Highlights: Porosity of chickpea was determined. Density of chickpea increases at the first period of soaking partly due to porosity. Swelling is more relevant after the first period. Water gain was found to be relevant up to a solids loss of 5% particularly at 25 °C. Ordinary diffusion was used to predict water and solids transfer.